Project of an anthropomorphic manipulator for the CAMBADA@Home robot - Santos, Luís Filipe Pereira Almeida (2014)
Nowadays, service robots are an attractive that moves numerous researchers and hence research units, publics or privates ones, being Universities a good example of this fact. RoboCup competition, namely its RoboCup@Home league, brings to the fore various and excellent projects, being a storefront of the service robots state of the art. Service robots have numerous applications, for instance serving someone for leisure, helping someone with reduced mobility or even perform boring tasks. In this sense, the Transverse Activity on Intelligent Robotics (ATRI) group, part of the Institute of Electronics and Telematics Engineering of Aveiro (IEETA), intends at endowing the CAMBADA@Home robot with an anthropomorphic arm. This arm allow a more e ective human robot interaction. Thus, the robot will be able to carry some small objects as well as put them in a predetermined place. Furthermore, this anthropomorphic manipulator will enable the robot to carry heavier loads with human cooperation as well as open doors. Herewith, this document depicts the conception of an anthropomorphic arm mechanical structure as well as the low level electronics developed on behalf of the arm right performance.